PANDE BESI DI ERA MODERN (Studi di Desa Sawan, Kecamatan Sawan, Kabupaten Buleleng) - Hartawan, I Gusti Made Dharma; Wiratni, Komang Ayu (Komunitas Manajemen Kompetitif, 2023)
The problem studied in this study is how do blacksmith craftsmen maintain their existence in themodern era in Sawan Village, Sawan District, Buleleng Regency. The method used is descriptive qualitativemethod with data collection techniques through observation, interviews, and documentation. There are 3(three) research findings on how blacksmith craftsmen maintain their existence in the modern era: First,continuing the parents' business with the inheritance process in continuing this business the blacksmithfamily in Sawan Village has a strategy of involving children in the blacksmith production process. Second,the opportunity for the blacksmith business to meet the necessities of life, namely the opportunity to becomea blacksmith craftsman by the Soroh Pande community in Sawan Village is influenced by production thathas lived from time to time and the products made already have quality so that there are always collectorswho come to look for them. products made by pande craftsmen in Sawan Village. Third, feeling proud to bea descendant of Pande, namely pride in being a Pande citizen as a form of devotion is manifested in twoways, namely through physical and symbolic activities. Physical activities are in the form of work, place ofwork and objects, while symbolic are names, colors and traditions.